Hybrid LES/RANS Simulations of a 90° Pipe Bend Using Different CFD Solvers - Ekat, Ann-Kathrin; Weissenbrunner, Andreas; Straka, Martin; Eichler, Thomas; Oberleithner, Kilian (OpenFOAM® Journal, 2023)
In this study, the performance of several RANS and hybrid LES/RANS turbulence models along with different CFD solvers (ANSYS Fluent, OpenFOAM and RapidCFD) is tested in terms of their ability to reproduce the flow downstream of a 90° pipe bend. The focus is on the temporal mean profiles downstream of the bend up to approximately 31 times the pipe’s diameter D. The turbulence models’ accuracy is evaluated by means of performance indicators and flow profiles in comparison to LDA measurements. The results demonstrate that the use of RANS models is suitable as long as the location of interest is in the vicinity of the bend up to approximately 10 D downstream of the bend. With increasing distance, the accuracy of the RANS models decreases, and the use of hybrid LES/RANS models is recommended. Three hybrid LES/RANS models are tested: the stress-blended eddy simulation (SBES) model as well as the Spalart-Allmaras-based and the k-omega SST-based improved delayed detached eddy simulation (IDDES) models. All three models show enhanced results for a distance to the bend >10 D. Additionally, it is found that in this geometry configuration, the IDDES models require a transient inlet. The flow separation due to the redirection inside the bend is too weak to generate turbulent fluctuations and a fast transition to full LES mode in the separation region. Due to the turbulent excitation at the inlet, the RANS region downstream of the bend is distinctly reduced, resulting in an enhanced performance of the hybrid IDDES models.